Employment Training — A Government Perspective - Dodge, David A.; Wilkinson, Lynn E. (Canadian Journal of Higher Education, 1982)
Federal involvement in employment training, from the establishment of the Royal Military College in 1884 to the legislation of the National Training Program in 1982, has been to ensure a qualified Canadian labour force. The evolving Canadian economy and the changing world of work have required a federal role varying from passive financing to direct training involvement. An examination of current and future demographic and employment trends, altered demand patterns, changing technology, new challenges of employment and unemployment, and a narrowing global community; in Federal reports and papers indicates that a com- prehensive, cooperative human resource strategy is essential to Canadian econo- mic health and international competitiveness.